2019
DOI: 10.1063/1.5093016
|View full text |Cite
|
Sign up to set email alerts
|

Obliquely propagating nonlinear ion-acoustic solitary and cnoidal waves in nonrelativistic magnetized pair-ion plasma with superthermal electrons

Abstract: The nonlinear propagation of ion-acoustic waves is considered in a magnetized system of collisionless and dissipative pair-ion plasma, composed of cold positively and negatively charged nonrelativistic ions, with superthermal electrons. obliquely propagating ion-acoustic solitary and cnoidal waves are investigated via a mechanical-motion analog Korteweg de Vries (KdV) approach. The characteristics of the emerged nonlinear magnetized waves are significantly modified by the effects of plasma parameters like the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We use the variable χ = η − UT, to determine the solution to KdVB equation (11), where χ is the transformed coordinate relative to a reference frame moving at the shock speed U. Equation (11) with respect to χ is integrated to produce…”
Section: Solution Of Kdv Burgers Equationmentioning
confidence: 99%
“…We use the variable χ = η − UT, to determine the solution to KdVB equation (11), where χ is the transformed coordinate relative to a reference frame moving at the shock speed U. Equation (11) with respect to χ is integrated to produce…”
Section: Solution Of Kdv Burgers Equationmentioning
confidence: 99%
“…We follow the same procedure in Refs. [50,53] and [54] to find the cnoidal wave solution of the obtained KdV Eq. ( 14) for DA waves.…”
Section: Nonlinear Periodic Wave Solutionsmentioning
confidence: 99%
“…[ 3 ] Experimental studies of ion‐acoustic waves (IAWs) in negative‐ion plasmas were reported by Song et al [ 4 ] and Wong et al [ 5 ] Linear and nonlinear properties of IAWs have been widely investigated theoretically by authors. [ 6–13 ] In the presence of dust impurities in the ordinary plasma, IAWs lead to the so‐called dust‐ion acoustic waves (DIAWs). [ 14 ] The propagation of DIAWs in an inhomogeneous dusty plasma was shown.…”
Section: Introductionmentioning
confidence: 99%